2021
DOI: 10.1186/s12885-021-08520-1
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis for identification of early diagnostic biomarkers and prognostic biomarkers of liver cancer based on GEO and TCGA databases and studies on pathways and biological functions affecting the survival time of liver cancer

Abstract: Background Liver cancer is the sixth most commonly diagnosed cancer and the fourth most common cause of cancer death. The purpose of this work is to find new diagnostic biomarkers or prognostic biomarkers and explore the biological functions related to the prognosis of liver cancer. Methods GSE25097 datasets were firstly obtained and compared with TCGA LICA datasets and an analysis of the overlapping differentially expressed genes (DEGs) was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 38 publications
4
30
0
Order By: Relevance
“…The Log-rank test revealed that high expression of TOP2A was a risk factor in ACC, KIRC, KIRP, LGG, LIHC, LUAD, MESO, PAAD and SCKM, and a protective factor in COAD and THYM. Part of these findings are consistent with other studies 8 , 27 29 , but the most of these results derived from the analysis of TCGA or GEO transcriptome data. However, some studies verified that the higher expression of TOP2A has nothing to do with the worse prognosis in these cancer types.…”
Section: Discussionsupporting
confidence: 90%
“…The Log-rank test revealed that high expression of TOP2A was a risk factor in ACC, KIRC, KIRP, LGG, LIHC, LUAD, MESO, PAAD and SCKM, and a protective factor in COAD and THYM. Part of these findings are consistent with other studies 8 , 27 29 , but the most of these results derived from the analysis of TCGA or GEO transcriptome data. However, some studies verified that the higher expression of TOP2A has nothing to do with the worse prognosis in these cancer types.…”
Section: Discussionsupporting
confidence: 90%
“…The same results are seen in all datasets. In recent years, studies have reported that NUSAP1 was involved in malignant pleural mesothelioma (MPM) [ 34 ], liver cancer [ 35 ], prostate cancer [ 36 ], and other cancers, with diagnostic value. We used the THCA dataset and analyzed the GSE27155, GSE33630, GSE58545, and GSE60542 datasets to demonstrate that NUSAP1 has a better diagnostic value in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have examined the correlation between the expression of these six genes and LT. ATP1A1, which regulates mitochondrial metabolism, is involved in the progression of nonalcoholic fatty liver disease or nonalcoholic steatohepatitis before and after LT. [35,36] LTBP4, which accumulates in the extracellular matrix of patients with stage F3 liver fibrosis, is reportedly involved in the activation of transforming growth factor beta (TGFβ) and induction of liver cirrhosis, while suppression of LTBP4 or FOSB promotes cell proliferation. [37,38] In neuroblastoma, LRRN2 was correlated with cell proliferation in the JNK pathway. [39] This suggested that cell proliferation may be regulated by various factors in the liver, and further studies are needed to determine whether suppression of LTBP4 or FOSB may promote hepatocyte proliferation in grafts and improve graft survival in LDLT.…”
Section: Discussionmentioning
confidence: 99%